Analysis model of the sustainability development of manufacturing small and medium- sized enterprises in Taiwan. (10th January 2019) - Chang, An-Yuan; Cheng, Yen-Tse
Abstract: To maintain competitiveness in the marketplace, enterprises have considered sustainability development as an important goal and initiated numerous strategies for sustainability. The three main dimensions, namely, economic, social and environmental aspects, have become the focus of the sustainable development of enterprises while serving as vital indicators for enhancing competitiveness. However, prior studies on sustainable development primarily emphasised theoretical discussions, and few scholars have conducted quantitative data analysis, especially in the small and medium-sized enterprises (SMEs) area. Given this research gap, this study developed an integrated multi-attribute decision analysis model to evaluate the sustainability development of manufacturing SMEs in Taiwan. The present research identifies key sustainability indicators that play a vital role in boosting the sustainable performance of manufacturing SMEs. Graphical abstract: Through reviewing the literature of the triple bottom line (TBL) performance indicators, Fuzzy Delphi Method (FDM) is used for the selection of the sustainability performance indicators. The sustainability performance evaluation model is developed by the entropy weighted GRA method. Then, neighbourhood rough set theory (RST) is used to assess the implementation of sustainability development for SMEs. Finally, sensitivity analysis is employed to observe the critical factors that affect performance. Image Highlights: Building practical implementation knowledge or provide management tools of sustainability development for SMEs are essential. An integrated MADM model is employed to evaluate and analyse the sustainability development of manufacturing SMEs. Key factors to enhance the effectiveness of sustainability development are identified.